Practical methods for analysis and design of HV installation grounding systems - Popovic, Ljubivoje M., 1944- (Academic Press, 2018)
Practical Methods for Analysis and Design of HV Installation Grounding Systems gives readers a basic understanding of the modeling characteristics of the major components of a complex grounding system. One by one, the author develops and analyzes each component as a standalone element, but then puts them together, considering their mutual disposition, or so-called proximity effect. This is the first book to enable the making and analysis of the most complex grounding systems that are typical for HV substations located in urban areas that uses relatively simple mathematical operations instead of modern computers. Since the presented methods enable problem-solving for more complex issues than the ones solved using National, IEC and/or IEEE standards, this book can be considered as an appendix to these standards.